2016
DOI: 10.1186/s12955-016-0564-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of shift and night work on health related quality of life of working women: findings from the Korea Health Panel

Abstract: BackgroundNight and shift work status has been associated with health related quality of life (HRQoL) in economically active women. This study aimed to investigate the association between night or shift work status and HRQoL of economically active women and to further analyze how marital status interplays in the objected relationship.MethodsData were from the Korea Health Panel, 2011 to 2013. A total of 2238 working women were included for analysis. Work status was categorized into day work, night work, and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
1
23
0
4
Order By: Relevance
“…It was found that most of the nurses with higher education e.g., graduation/post-graduation more involved in fixed/morning duty, while nurses with relatively less education were more prevalent in rotational duties. Similar to the studies conducted in Italy, Egypt, and Korea in 2016 21-23. Our study also showed a significant association between education level and duty shift (p-value 0.007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was found that most of the nurses with higher education e.g., graduation/post-graduation more involved in fixed/morning duty, while nurses with relatively less education were more prevalent in rotational duties. Similar to the studies conducted in Italy, Egypt, and Korea in 2016 21-23. Our study also showed a significant association between education level and duty shift (p-value 0.007).…”
Section: Discussionsupporting
confidence: 90%
“…These findings were supported by the studies conducted in Italy18 and Egypt21 in 2016. Another study accomplished among Korea health panel in 2016, found age as a significant factor between shifting and rotational duties 23. However, a study conducted among Tunisian nurses in 2017 did not support this finding 24.…”
Section: Discussionmentioning
confidence: 96%
“…Some will naturally adopt an effective leadership style, while others may find the concept of leadership or seeing themselves as leaders difficult to understand [ 11 ]. It is of paramount importance to explore and fully understand the potential determinants of psychological well-being in nurses [ 21 - 23 ]. Quality of life (QOL) concept has been recognized as a relevant measure of well-being in various healthy populations, including workers [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] A study among more than 2000 women in Korea showed that working in rotating shift or night shift was associated with significantly poor healthrelated quality of life (HRQoL). 12 HRQoL is defined as the way health is empirically estimated to affect QoL. 13 Sleep disturbance is a common problem faced by night-shift workers.…”
Section: Introductionmentioning
confidence: 99%